2013
DOI: 10.1080/09654313.2013.814621
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge That Matters: Identifying Regional Knowledge Assets of the Tampere Region

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Specific factors for regional knowledge management were studied well in the past. For example, knowledge as a key component of a region's development [18], [19], industrial development in the peripheral regions on the basis of knowledge management [20] and formation of knowledge infrastructure for the purpose of developing a region's innovative activities [21] are components of the triple helix, interactions in the space of institutional areas [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specific factors for regional knowledge management were studied well in the past. For example, knowledge as a key component of a region's development [18], [19], industrial development in the peripheral regions on the basis of knowledge management [20] and formation of knowledge infrastructure for the purpose of developing a region's innovative activities [21] are components of the triple helix, interactions in the space of institutional areas [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This qualitative 3P1C framework has been partially applied in a study investigating knowledge assets in the context of Tampere Region, Finland (see Lonnqvist et al, 2014). The research aimed to explore how the relevant knowledge assets can be identified for a given region and to describe what the context-specific knowledge assets are.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…In essence, this approach takes the view that knowledge is a key construct for understanding the means and modes of urban development (Yigitcanlar 2009), with an explicit focus on identifying the knowledge assets of urban environments (Kunzmann 2008;Lönnqvist et al 2013). Consequently, the starting point for this paper is the argument that the development path of a city economy is dependent upon the quality of the urban innovation system it possesses and the knowledge based assets within it.…”
Section: Introductionmentioning
confidence: 99%
“…At the urban and city level the notions of 'knowledge cities' (Carrillo 2004;Carrillo 2006;Yigitcanlar & Velibeyoglu 2008) and 'knowledge-based urban development' (Knight 1995;Knight 2008;Kunzmann 2008;Yigitcanlar & Lönnqvist 2013;Yigitcanlar 2009) have emerged as a means of examining in a systematic manner the role of knowledge and networks as key components of urban economic evolution. In particular, the knowledge city concept takes a broad view of knowledge as a key construct for understanding the means and modes of urban development (Yigitcanlar 2009), with an explicit focus on identifying the knowledge assets of urban environments (Kunzmann 2008;Lönnqvist et al 2013). The knowledge city and knowledge-based urban development schools of thought encompass the knowledge construct within a framework that seeks to integrate the economic, social, and environmental assets and factors underpinning development (Yigitcanlar 2009;Yigitcanlar 2010).…”
mentioning
confidence: 99%